Cell phone case playing buffering role - CHEN DONGNI (2013)
The utility model relates to a cell phone case playing a buffering role, and the cell phone case is characterized by consisting of an upper wall (7), a lower wall (4), a left wall (1), a right wall (6), a bottom wall (5) and a cover wall (2); the upper wall (7), the lower wall (4), the left wall (1), the right wall (6), the bottom wall (5) and the cover wall (2) are connected into a whole and a space which is enclosed by the walls is in a rectangular shape; and the middle part of the cover wall (2) is provided with an inlet and outlet hole (3). A bar phone can be arranged in the cell phone case and calls can be made; if people drop the cell phone onto the ground carelessly, the cell phone case can play the buffering role, the impact force between the cell phone and the ground is reduced, so that the damage degree of the cell phone is minimized and even the cell phone is not damaged; when being not in use, the cell phone is not directly contacted with an external object, so that wear is prevented; and accordin